Appendiceal goblet cell carcinoids and adenocarcinomas ex-goblet cell carcinoid are genetically distinct from primary colorectal-type adenocarcinoma of the appendix - Jesinghaus, Moritz; Konukiewitz, Björn; Foersch, Sebastian; Stenzinger, Albrecht; Steiger, Katja; Muckenhuber, Alexander; Groß, Claudia; Mollenhauer, Martin; Roth, Wilfried; Detlefsen, Sönke; Weichert, Wilko; Klöppel, Günter; et al. (Modern pathology, 2018)
The appendix gives rise to goblet cell carcinoids, which represent special carcinomas with distinct biological and histological features. Their genetic background and molecular relationship to colorectal adenocarcinoma is largely unknown. We therefore performed a next-generation sequencing analysis of 25 appendiceal carcinomas including 11 goblet cell carcinoids, 7 adenocarcinomas ex-goblet cell carcinoid, and 7 primary colorectal-type adenocarcinomas, using a modified Colorectal Cancer specific Panel comprising 32 genes linked to colorectal and neuroendocrine tumorigenesis. The mutational profiles of these neoplasms were compared with those of conventional adenocarcinomas, mixed adenoneuroendocrine carcinomas, and neuroendocrine carcinomas of the colorectum. In addition, a large-scale pan-cancer sequencing panel covering 409 genes was applied to selected cases of goblet cell carcinoid/adenocarcinoma ex-goblet cell carcinoid (n=2, respectively). Mutations in colorectal cancer-related genes (eg, TP53, KRAS, APC) were rare to absent in both, goblet cell carcinoids and adenocarcinomas ex-goblet cell carcinoid, but frequent in primary colorectal-type adenocarcinomas of the appendix. Additional large-scale sequencing of selected goblet cell carcinoids and adenocarcinomas ex-goblet cell carcinoid revealed mutations in Wnt-signaling-associated genes (USP9X, NOTCH1, CTNNA1, CTNNB1, TRRAP). These data suggest that appendiceal goblet cell carcinoids and adenocarcinomas ex-goblet cell carcinoid constitute a morphomolecular entity, histologically and genetically distinct from appendiceal colorectal-type adenocarcinomas and its colorectal counterparts. Altered Wnt-signaling associated genes, apart from APC, may act as potential drivers of these neoplasms. The absence of KRAS/NRAS mutations might render some of these tumors eligible for anti-EGFR directed therapy regimens.
Gesehen am 19.11.2019